Porcine Beta-Defensin 2 Provides Protection Against Bacterial Infection by a Direct Bactericidal Activity and Alleviates Inflammation via Interference With the TLR4/NF-κB Pathway - Huang, Chao; Yang, Xi; Huang, Jing; Liu, Xiao; Yang, Xiaoyu; Jin, Hui; Huang, Qi; Li, Lu; Zhou, Rui (Frontiers in Immunology, 2019)
Porcine beta-defensin 2 (PBD-2) which is a member of the family of antimicrobial peptides, is widely expressed in pig organs with a broad spectrum of bactericidal activities confirmed in vitro. We previously demonstrated that transgenic (TG) pigs overexpressing PBD-2 could resist the infection by the porcine pathogen Actinobacillus pleuropneumoniae. In this study, the roles of PBD-2 in protecting against bacterial infection were further investigated. The biochemical indexes of the blood sample, body weights, histological morphologies and weights of the organs of TG mice expressing PBD-2 were measured. Results confirmed that these mice showed normal physiological features. An assay of Salmonella Typhimurium infection was conducted on wild-type (WT) and TG mice. The TG mice possessed higher survival rate, less body weight loss and pathological changes and smaller recovery rates of bacteria after infection with Salmonella Typhimurium. The in vitro synthetic PBD-2 and the serum and tissue homogenates from the TG mice displayed a direct bactericidal activity. Moreover, PBD-2 could inhibit the release of the proinflammatory cytokines, including IL-6, TNF-α, IL-1β and IL-12, in the TG mice infected with S. Typhimurium or treated with lipopolysaccharide (LPS). The WT mice treated with PBD-2 and S. Typhimurium or LPS showed reduced levels of proinflammatory cytokines. The mouse macrophage cell line RAW 264.7 which expressed PBD-2 was constructed to detect the signal pathways affected by PBD-2. The suppressing effect of PBD-2 on the release of the proinflammatory cytokines was confirmed using RAW 264.7 either expressing PBD-2 or supplemented with PBD-2. The promoter activity and mRNA level of NF-κB were detected, and PBD-2 was shown to significantly inhibit the activation of the NF-κB pathway induced by LPS. The direct interaction of PBD-2 with TLR4 was revealed by isothermal titration calorimetry and far-Western blot in vitro and the coimmunoprecipitation of PBD-2 with TLR4 on RAW 264.7 cells. This interaction indicates one reason for the interference of NF-κB activation. Overall, this study showed that PBD-2 protected against bacterial infection through a direct bactericidal activity and alleviated inflammation by interfering with the TLR4/NF-κB pathway.